Análisis de la interpretación del artículo 230 de la Constitución Nacional, en las providencias de tutela de la Corte Suprema de Justicia (2007-2009) - Gómez Martínez, Diego León (2023)
The Colombian Supreme Court ‘s opinions have interpreted section 230 of the Constitution formalistically, and this has led to a biased construal of that provision . In several opinions , the Supreme Court has dismissed writs of protection of fundamental rights filed against its own opinions, and it has done so based on an ant iquated understanding of law.